2016
DOI: 10.3847/0067-0049/224/2/35
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Measured Radiative Lifetimes and Oscillator Strengths in Neutral Vanadium

Abstract: We report a new study of the V I atom using a combination of time-resolved laser-induced fluorescence and Fourier transform spectroscopy that contains newly measured radiative lifetimes for 25 levels between 24,648 cm −1 and 37,518 cm −1 and oscillator strengths for 208 lines between 3040 and 20000 Å from 39 upper energy levels. Thirteen of these oscillator strengths have not been reported previously. This work was conducted independently of the recent studies of neutral vanadium lifetimes and oscillator stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Lawler et al (2014;hereafter La14) reported new transition probabilities for 836 V I lines. Recently, Holmes et al (2016;hereafter Ho16) have also determined transition probabilities for 208 lines of this species. For most lines in common between these two studies the results are in good agreement, but Ho16 suggest that the La14 log(gf) values are systematically too small for six lines in common near 900 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Lawler et al (2014;hereafter La14) reported new transition probabilities for 836 V I lines. Recently, Holmes et al (2016;hereafter Ho16) have also determined transition probabilities for 208 lines of this species. For most lines in common between these two studies the results are in good agreement, but Ho16 suggest that the La14 log(gf) values are systematically too small for six lines in common near 900 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting log(gf)s for V I confirmed a good Saha balance for V in the Sun and HD 84937 [58]. A recent challenge by Holmes et al [59] to the BFs and log(gf)s for six of the 836 lines in Lawler et al [58] is under review. The tentative conclusions of the review confirmed the accuracy of Ar I branching ratios [60] used for calibration of FTS data and support the accuracy of the log(gf)s in Lawler et al [58].…”
Section: Lab Astro Results From the Univ Of Wisconsin -Madison Iclmentioning
confidence: 74%
“…The subsequent term analysis led to 544 accurate energy levels, of which 89 were new, found for the first time (Thorne et al 2011). We also measured transition probabilities for 208 lines in the range 304-2000 nm from 39 upper levels by combining our FTS measured relative line intensities and atomic level lifetimes, measured at Lund laser centre, (Holmes et al 2016), increasing the number of laboratory loggf s available at longer wavelengths. V II -our published linelist includes 1242 classified lines in the 149-580 nm range from FT spectra.…”
Section: Vanadiummentioning
confidence: 99%